The role of the Kepong Guidance Center in shaping the character of students and fostering a noble Islamic generation - Meitania Affandi; Ikhwan Fauzi Nasution; Ardhana Januar Mahardhani; Hadi Cahyono; Sunarto Sunarto (STAI Hubbulwathan Duri, 2023)
Noble character is very important for students, and this research will see how each student's character develops. Kepong Guidance Center is a place of study for undocumented Indonesian students living in Malaysia. This consultancy studio supports the teaching of Indonesian students in Malaysia. This article is structured as follows: 1) Religious education is very important to develop students' morally upright character. However, because everyone's temperament varied greatly, it was common for students to get along badly, 2) The aim of this study is to investigate the role of the Kepong Guidance Center in shaping the character of students. 3) This study used qualitative approach and the method of the data collection was using observations and interviews. 4) engage in activities that help children develop their character and adopt noble attitudes, such as placing them in groups to plan lessons and encourage sharing. 5) Based on the findings above, it can be concluded that the teachers at Kepong Guidance Center play a crucial role in shaping the character of students and fostering a noble Islamic generation. The study showed that the students' character improved swiftly and that they found it easy to understand and practice what had been taught and guided. However, many students still require additional instruction to further develop their admirable character traits, and many pupils at the Kepong Guidance Center face challenges in their homes.